IMPLEMENTASI MEDIA AUDIO-VISUAL DALAM PEMBELAJARAN ISTIMA‘ DI MA. HASYIM ASY’ARI JOGOROTO KELAS 10 (April & October, 2025)
Listening is a fundamental ability that humans possess from birth and continue throughout life. However, in the context of language learning, there is a problem of low student interest in Istima' learning. Therefore, this study aims to describe the process of implementing the audio-visual method in Istima' learning for students at MA Hasyim Asy'ari Jogoroto, Class 10. This research is qualitative and descriptive in nature, using observation and documentation as instruments. The subjects and objects of this research are the students of MA Hasyim Asy'ari Jogoroto. The results of the study show that the Istima' learning process with the well-prepared audio-visual method includes: a) teacher planning, which involves preparing relevant materials, b) students watching the videos presented, c) students noting down vocabulary (mufrodat) from the videos, d) students summarizing the story from the video using Arabic, e) students deriving lessons (hikmah) from the video, and f) the evaluation process in this study consists of two parts: first, a written evaluation (students submit their vocabulary notes from listening), and second, an oral evaluation (students communicate directly in Arabic to provide a summary and lesson learned from the video). The implementation of Istima' learning with the audio-visual method successfully created a more engaging atmosphere and enhanced student participation in the learning process.